The Octadecanoid Pathway, but Not COI1, Is Required for Nectar Secretion in Arabidopsis thaliana - Schmitt, Anthony J.; Roy, Rahul; Klinkenberg, Peter M.; Jia, Mengyuan; Carter, Clay J. (Frontiers in Plant Science, 2018)
Over 75% of crop species produce nectar and are dependent on pollinators to achieve maximum seed set, yet little is known about the mechanisms regulating nectar secretion. The phytohormone jasmonic acid (JA) is recognized to be involved in several plant processes including development and defense. JA was also recently shown to positively influence nectar secretion in both floral and extrafloral nectaries. For example, endogenous JA levels peak in flowers just prior to nectar secretion, but the details of how JA regulates nectar secretion have yet to be elucidated. We have found that the octadecanoid pathway does indeed play a role in the production and regulation of floral nectar in Arabidopsis. Null alleles for several JA biosynthesis and response genes had significantly reduced amounts of nectar, as well as altered expression of genes known to be involved in nectar production. We additionally identified crosstalk between the JA and auxin response pathways in nectaries. For example, the nectar-less JA synthesis mutant aos-2 showed no auxin response in nectaries, but both nectar production and the auxin response were restored upon exogenous JA and auxin treatment. Conversely, coi1-1, a JA-Ile-insensitive receptor mutant, displayed no auxin response in nectaries under any circumstance, even in older flowers that produced nectar. Surprisingly, opr3-1, a mutant for 12-oxophytodienoate reductase 3 [(an enzyme further down the JA biosynthetic pathway that reduces 12-oxo phytodienoic acid (OPDA)], produced no nectar in newly opened flowers, but did secrete nectar in older flowers. Furthermore, a similar phenotype was observed in coi1-1. Cumulatively, these observations strongly suggest an indispensable role for an octadecanoic acid- and auxin-dependent, but JA- and COI1-dispensible, pathway in regulating nectar production in Arabidopsis.